The The Effect of Profitability, Leverage, Liquidity, Firm Growth on Dividend Policy with Firm Size as Moderating Variable in infrastructure companies listed on The Indonesian Stock Exchange period 2018-2022 - Fitriyah, Berlian (Jurnal Ilmu Manajemen, 2024)
This research aims to determine the effect of profitability, leverage, liquidity, and firm growth on dividend policy with firm size as a moderating variable in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) period 2018-2022. The type of data used is quantitative data from secondary sources. The population in this study is 61 infrastructure sector companies listed on the IDX from 2018 to 2022. The purposive sampling technique was used to determine the research sample, and 24 companies were obtained as the research sample. The data analysis technique used is path analysis with AMOS 24 software. The results of the study show that profitability, leverage, and firm growth do not have a significant effect on dividend policy. Liquidity has a significant positive effect on dividend policy. Firm size cannot significantly moderate the effect of profitability and leverage on dividend policy. Firm size can weaken the effect of liquidity on dividend policy. Therefore, companies in the infrastructure sector must pay attention to the company's liquidity level because it can positively affect the amount of dividend payments. Especially for large companies, they must maintain their liquidity level to remain optimal because a high level of liquidity does not guarantee that a company can easily pay dividends to shareholders.